Influences of Country of Origin (COO) and branding on product evaluation : a case study of the international cruise industry - Chew, Pei Ling (2008)
This study examines the effects of both brand and country of origin effects on the quality perception, attitude and purchase intention of cruise ship consumers. Royal Caribbean Lines and Star Cruise were used in the case study.